2019
DOI: 10.1080/16078454.2019.1687144
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in deep vein thrombosis: a therapeutic target?

Abstract: Deep vein thrombosis is a common disease associated with a variety of complications including post-thrombotic syndrome as a late complication. It is now clear that in addition to classical deep vein thrombosis triggers such as blood flow disturbance, hypercoagulability, and vessel wall changes, inflammation has a key role in the pathophysiology of deep vein thrombosis, and there is a close relationship between inflammation and coagulation. As attested by changes in several plasma biomarkers, inflammation may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 101 publications
(120 reference statements)
2
32
0
2
Order By: Relevance
“…Increasing evidences have showed that in ammatory response played an important role in the development of DVT. Acute DVT causes a systemic in ammatory response characterized by elevated in ammatory factors and temporal accumulation of in ammatory cells including white blood cells [43,44]. Dawei Liu et al studied 1179 patients of tibial plateau fractures, and found that platelet and neutrophil count were independently associated with elevated D-dimer levels [45].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences have showed that in ammatory response played an important role in the development of DVT. Acute DVT causes a systemic in ammatory response characterized by elevated in ammatory factors and temporal accumulation of in ammatory cells including white blood cells [43,44]. Dawei Liu et al studied 1179 patients of tibial plateau fractures, and found that platelet and neutrophil count were independently associated with elevated D-dimer levels [45].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, anticoagulant drugs such as LMWHs have demonstrated the direct potential of their anti-inflammatory capabilities in addition to their anticoagulant properties (37). Moreover, the involvement of inflammation in the pathophysiology of the venous thrombotic process has been clearly established (38). Inflammation is a very interesting tool for evaluating the potential of the new anti-thrombotic drugs (DOACs) targeted to inhibite or reduce inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences have showed that inflammatory response played an important role in development of DVT. In fact, coagulation activation and inflammation reaction are intimately related because multiple cellular factors are involved in both processes, including but not limited to monocyte, neutrophils, and platelets [28][29][30]. In an animal experiment, Bruhl et al [30] demonstrated the monocytes, neutrophils, and platelets cooperated to initiate and propagate venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%